Guerrilla Gardening in a Time of Ecological and Social Crisis: An Exploratory Endeavor to Feel Connected with a Lost Piece of Forest - Häggström, Margaretha; Häggström, Mårten (The Trumpeter, 2024)
This four-year explorative study is located in a nearby forest, or more accurately a clearcut, in the western part of Sweden. The objective is to contribute to existing knowledge about forest gardening by exploring a forest milieu without trees in the Northern Hemisphere where the conditions are poor. The aim is to support biodiversity in the short term and to find out whether we could cultivate root vegetables, potatoes, and summer flowers in this nutrient-poor and shadowless environment. The study has an eco-philosophical approach that promotes eco-pedagogy and environmental education and a pragmatic pedagogical approach that adopts a "learning-by-doing" belief. The exploration is underpinned by collaborative autoethnography, and the research is conducted in and through practice. The findings show that a planting project in a clearcut requires a lot of preparation and planning and that it is possible to use a clearcut to grow potatoes, peas, and some summer flowers without special efforts, but hard to grow other crops such as vegetables and root vegetables. The project implies that the planting activities in a clearcut may have a deep impact on people’s sense of human-nature identity and respect for the natural environment.